PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERJUDIAN SECARA ONLINE DI KOTA PARIAMAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Article 45 paragraph (1) of Law Number 11 of 2008 concerning Electronic Transaction Information states that Anyone who meets the elements referred to in Article 27 paragraph (1), paragraph (2), paragraph (3), or paragraph (4) shall be punished with a maximum imprisonment of 6 (six) years and / or a maximum fine of Rp. 1,000,000,000 (one billion rupiah). But in fact the application of the criminal sanctions has not run optimally, because this can be seen from the many cases of online gambling that have occurred in Kota Pariaman. This easy access to online gambling makes anyone able to gamble, be it adults or children. And also the lack of government supervision of online gambling provider sites, especially online lottery gambling. This study aims to determine law enforcement, constraints and causes of online gambling crime in Kota Pariaman.This type of research can be classified in the type of sociological research, because in this study the author directly conducted research into the location or field of the place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pariaman Police, while the population and sample were all parties related to the problem studied. In this study, the data sources used were primary data. Secondary data and tertiary data. Data collection techniques in this study were interviews and literature study.From the results of the study, there are three main things that can be concluded that law enforcement carried out by the Pariaman Police is by means of preventive efforts and refractory efforts, while the obstacles faced by the police are the limited human resources (HR) of the police. understand information and technology and the lack of adequate facilities and infrastructure to support the performance of the police in this online gambling case. The causative factors for this crime are adequate facilities for someone to commit a criminal offense, limited human resources and also economic factors that can trigger someone to do this online gambling Keywords: Law Enforcement - Crime - Online Gambling